2014
DOI: 10.1093/carcin/bgt492
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette sidestream smoke induces histone H3 phosphorylation via JNK and PI3K/Akt pathways, leading to the expression of proto-oncogenes

Abstract: Post-translational modifications in histones have been associated with cancer. Although cigarette sidestream smoke (CSS) as well as mainstream smoke are carcinogens, the relationship between carcinogenicity and histone modifications has not yet been clarified. Here, we demonstrated that CSS induced phosphorylation of histones, involving a carcinogenic process. Treatment with CSS markedly induced the phosphorylation of histone H3 at serine 10 and 28 residues (H3S10 and H3S28), which was independent from the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
3
48
0
1
Order By: Relevance
“…4a–c) have shown no difference in the relative level of cyclins, mitotic index, and cell cycle profile between tumor and paired negative resection margin tissues, thus strongly suggesting that an increase of H3S10ph is independent of G2/M cell cycle phase in GC. A recent report has also shown a cell cycle-independent cigarette side-stream smoke-induced increase of H3S10ph leading to the overexpression of proto-oncogenes, c-jun and c-fos , and tumor promotion [18]. Further, our study also showed the presence of maximum percentage of cells in the G1 phase of the cell cycle (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…4a–c) have shown no difference in the relative level of cyclins, mitotic index, and cell cycle profile between tumor and paired negative resection margin tissues, thus strongly suggesting that an increase of H3S10ph is independent of G2/M cell cycle phase in GC. A recent report has also shown a cell cycle-independent cigarette side-stream smoke-induced increase of H3S10ph leading to the overexpression of proto-oncogenes, c-jun and c-fos , and tumor promotion [18]. Further, our study also showed the presence of maximum percentage of cells in the G1 phase of the cell cycle (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, H3S10ph was taken for detailed study. To the best of our knowledge, several cell line- and animal model-based studies have shown increase in H3S10ph, as the only histone mark involved in carcinogenesis and cellular transformation [11, 1618]. However, there is no report on its relative level (tumor vs resection margin) and regulatory pathway in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of human pulmonary epithelial cells, histone H3 was more highly phosphorylated at serine 10 and 28 (H3S10 and H3S28) after exposure to formaldehyde compared with normal human lung fibroblasts [135, 136], particularly within the promoter region of the proto-oncogenes FOS and JUN , indicating a relationship between formaldehyde-inducted tumorigenesis and H3S10 and H3S28 phosphorylation. Another study demonstrated that binding of formaldehyde to lysine residues on histone 4 only occurred in the absence of post-translational modifications of histone 4, indicating that the balance between histone acetylation and deacetylation could be disturbed by the attachment of formaldehyde on lysine residues [137].…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…A549 cells treated with NNK were suspended in nuclear extraction buffer (5 mM Tris pH 7.5, 1 mM EDTA, 210 mM mannitol, 70 mM sucrose), and nuclear extracts were prepared as previously described (Ibuki et al, 2014). Nuclear protein samples were separated by 12.5% SDS-PAGE and blotted onto polyvinylidene fluoride membranes.…”
Section: Western Blot Analysis Of C-h2axmentioning
confidence: 99%